Disease Models & Mechanisms in the Age of Big Data - Antonis K. Hatzopoulos (The Company of Biologists, 2019)
In the decade since Disease Models & Mechanisms was launched, the emergence of Big Data as the main foundation of biological information is having a profound effect on how we do research and it has provoked some interesting questions. Is Big Data exploration replacing hypothesis-driven basic research? And, to what extent is disease modeling in the laboratory still relevant to medical research? Recent examples of synergistic approaches utilizing animal modeling and electronic medical records mining show that combining efforts between disease models and clinical datasets can uncover not only disease etiologies, but also novel molecular and cellular mechanisms linked to gene function.